(untitled) - Kotler, Philip (Hoboken, NJ, 2004)
Accurately identifying your target investor and effectively highlighting the strengths of your business are now critical to securing the support your business needs. From early-stage financing to borrowing money to issuing stock, Attracting Investors shows you how to market yourself and your business to raise funds, and explains why marketing is the key to successful capital raising. This comprehensive book will be essential for small start-ups, as well as established firms looking for new funding sources. The capital game has changed, and Attracting Investors is your guide to the new rules.
Keywords: Venture capital,Small business,New business enterprises,Doanh nghiệp mới; Finance,Finance,Tài chính